(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
For more than fifty years, researchers have strived hard to form a better understanding of impulse buying (Stern; 1962; Rook et.al; 1987; Rook and Fisher; 1995; Peck and Childers; 2006 ; Chang et.al; 2011). The purpose of this paper is to provide a detailed account of impulse buying behavior. The content analysis of various research work led to the classification of literature into various factors affecting impulse purchase decisions ,classifying products into impulse and non impulse items, behavior dimensions of impulse buying and Rook and Fisher (1995, p.305) proposed that consumers tend to control their innate impulsive tendencies as they perceive impulse buying as normatively wrong. This paper will be useful for practitioners and researchers towards understanding of impulsive behavior of consumers and will provide a better insight in.